2021
DOI: 10.7759/cureus.13958
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis at Onset of Pediatric Type-1 Diabetes Triggered by Covid-19: An Original Case Report

Abstract: During the course of this year, scientific research has revolved around coronavirus disease 2019 (COVID-19), with much uncertainty surrounding its pathogenesis, complications, and mortality as well as limited pediatric evidence. The exact relationship between COVID-19 and new-onset type 1 diabetes, especially in children, remains an unresolved issue. Our case exhibited a unique presentation of diabetic ketoacidosis (DKA) triggering COVID-19 diagnosis at this age. A three-year-old Moroccan boy was admitted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In a case series reported by Suwanwongse and Shabarek, three cases of newly diagnosed DM were associated with COVID-19, of which, two patients were diagnosed with DKA and the other came in with hyperglycemia after being diagnosed with COVID-19 [ 10 ]. Rabizadeh et al and Benyakhlef et al both reported cases of young patients with new-onset DM presenting as DKA; the latter being complicated by pneumonia [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a case series reported by Suwanwongse and Shabarek, three cases of newly diagnosed DM were associated with COVID-19, of which, two patients were diagnosed with DKA and the other came in with hyperglycemia after being diagnosed with COVID-19 [ 10 ]. Rabizadeh et al and Benyakhlef et al both reported cases of young patients with new-onset DM presenting as DKA; the latter being complicated by pneumonia [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following removal of duplicates and the exclusions, 20 studies were eligible for the systematic review (Figure 1). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Seven of the studies were conducted in Europe, five in USA, four in North Africa, and four in Asia (Table 1). In terms of design, two studies were case series and 18 were case reports In total, there were 37 cases of new onset T1D.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there were many reported cases of isolated diabetes insipidus as sequelae of COVID-19 viral infection without MRI abnormality. Furthermore, case reports of type 1 diabetes after COVID-19 infection have been also described [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%